Allochthonous versus autochthonous organic matter sustaining macroconsumers in a subtropical sandy beach revealed by stable isotopes. Issue 3 (16th March 2019) - Garcia, A. M.; Oliveira, M. C. L. M.; Odebrecht, C.; Colling, J. L. A.; Vieira, J. P.; Rodrigues, F. L.; Bastos, R. F.
ABSTRACT: Exchange of matter and energy between ecosystems has been an important topic in ecology. In this work, we estimated the relative assimilation and seasonality of autochthonous versus allochthonous organic matter by macrofauna and fishes of a subtropical sandy beach. Sampling of consumers and autotrophic food sources (particulate organic matter in suspension-POM and in sediment-SOM) were obtained seasonally at the sandy beach for carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analysis. The range in isotopic values of POM was nearly two-fold higher in winter than in other seasons, which coincided with similar decrease in δ 13 C values of several consumers. Such decreasing patterns in δ 13 C were associated with high rainfall and freshwater discharge during winter, which exported 13 C-depleted continental POM to the sandy beach. The continental allochthonous matter assimilated by marine organisms originated from the drainage of wetlands by innumerous coastal streams spread along the coast and by a larger estuarine system. Bayesian isotope mixing models revealed a slightly higher average assimilation of organic matter of the coastal streams (24%) than the estuary (18%). The assimilation of allochthonous matter was higher in filter feeders bivalves and detritivore fish and lower in carnivorous guilds (e.g. zoobenthivores, zooplanktivores, carnivorous and scavengers).